Atividade anestésica em robalos-peva (Centropomus parallelus) e caracterização química do óleo essencial das folhas de nectandra megapotamica (Spreng.) Mez (Lauraceae) - Tondolo, Juliana Simoni Moraes (2011)
The increasing expansion of aquaculture, the stress on the animals in farming systems and the adverse effects caused by conventional anesthetics has encouraged the search for natural anesthetics, safer, more effective, with lower side effects and less residual waste. In this context, this work aimed to evaluate the anesthetic potential of the essential oil (EO) from leaves of Nectandra megapotamica in fat snook (Centropomus parallelus) and its chemical composition. For extraction of the EO, the leaves were separated in young (EO-Y) or old (EO-O) and chemical composition analysis was performed by GC/MS. The major constituents of the Y and O-EOs were: bicyclogermacrene (46.5/34.6%), α-pinene (26.8/26.2%), β-pinene (7.9/12.3%), and germacrene D (9.6/9.1%). In the first experiment, four different concentrations of each EO were tested in fat snook acclimated to two salinities (zero and 33 ppt) to evaluate anesthesia induction and recovery time. In the second experiment, two concentrations of EO-O were tested in fish acclimated to both salinities for the evaluation of stress parameters (glucose, lactate, Na+ and K+ plasma levels) caused by handling. In the third experiment, the fish were transported in plastic bags, supplied with both water salinities and two concentrations of EO-O for evaluation of water quality and mortality after transport. Mild sedation was achieved at 30 μL L-1 and deep anesthesia at 150 μL L-1 with both EO. The EO-O was not able to avoid the stress of handling, as evidenced by elevated glucose and lactate plasma levels observed in all treatments and controls. The treatments did not change significantly the plasma Na+ and K+ levels in the fish kept at both salinities. During transportation, the use of EO-O did not improve the water quality and post-transport mortality. On the contrary, the fish transported with the highest concentration of EO-O in seawater had significantly higher mortality than the other groups. In conclusion, the EO of N. megapotamica at the tested concentrations was efficient to induce sedation and anesthesia in fat snook, but was not effective in preventing the stress generated by handling and transport of this species.